Musical Affordances and the Gestalt Legacy: enriching music perception - Klotz Sebastian (Gestalt Theory, 2023)
In the current cognitive theory of music, concepts of Gestalt psychology are referred to in various ways. For example, neurocognitive models of music perception address the formation of auditory Gestalts as a stage in the formation of meaning. However, this view runs counter to central premises of Gestalt psychology of Carl Stumpf’s school, which precisely did not describe Gestalts as synthesized phenomena. Nevertheless, it is argued here, borrowing from Gestalt concepts can promote current non-reductionist positions. They conceptualize musical perception not in the ways of information theory, but of phenomenology and action theory. Here the theory of affordance developed by J.J. Gibson in close collaboration with his wife Eleanor J. Gibson stands out. It was explicitly introduced into musicological research by Eric Clarke, but without reference to its Gestalt psychological roots. The article explores theories of musical affordance with the help of further methodological tools, which can be assigned to the philosophical schools of direct realism and constructivism. They open up the possibility of a non-cognitivist and non-representational perspective on musical perception. It turns out that Gestalt psychological concepts also have a catalytic effect on the expansion of our understanding of musical perception in this constellation, although this connection has hardly been visible so far.